2015
DOI: 10.1111/echo.13098
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pulmonary Artery Stiffness in Patients with Obstructive Sleep Apnea Syndrome

Abstract: Elastic properties of pulmonary artery deteriorate with severity of OSAS and may be responsible for right ventricular dysfunctions in OSAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…However, heterogeneity is to be expected given the variety of studies conducted by different teams at various geographic locations, the variation in disease severity, and differences in the patient populations. In most studies, the investigators were blinded to the participants' study group status [15, 16, 2127, 29, 31, 3335, 38, 39]. In addition, interobserver agreement and intraobserver reproducibility were assessed in most of the studies [15, 16, 21, 2325, 27, 29, 33, 36, 38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…However, heterogeneity is to be expected given the variety of studies conducted by different teams at various geographic locations, the variation in disease severity, and differences in the patient populations. In most studies, the investigators were blinded to the participants' study group status [15, 16, 2127, 29, 31, 3335, 38, 39]. In addition, interobserver agreement and intraobserver reproducibility were assessed in most of the studies [15, 16, 21, 2325, 27, 29, 33, 36, 38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings obtained for the aorta in OSAS patients were also reported for the pulmonary vascular bed. In patients with OSAS, Altıparmak et al revealed significantly impaired pulmonary artery distensibility that was also positively correlated with AHI (19).…”
Section: Discussionmentioning
confidence: 99%
“…The pulmonary artery elasticity is an important factor governing this relationship, with increased stiffness leading to higher right ventricular pulsatile work load, decreased contractile performance, and enhanced energy transmission to smaller pulmonary vessels, resulting in further vascular damage (23)(24)(25). A recent study by Altıparmak et al demonstrated also that pulmonary artery distensibility is associated with right ventricular systolic and diastolic parameters (19). They used right ventricular MPI, which is a global parameter of cardiac function combining both systole and diastole.…”
Section: Discussionmentioning
confidence: 99%
“…20 Although the relationship between them has not been fully explained, it was reported that the increase in PAS is an important factor contributing to RV afterload and eventual RV failure. [8][9][10][11][12][13][14] In this population, pulmonary diseases affecting the right heart, especially OSAS and COPD, may cause right heart dysfunction without PHT. [8][9][10][11][12][13][14] In this population, pulmonary diseases affecting the right heart, especially OSAS and COPD, may cause right heart dysfunction without PHT.…”
Section: Pas Is a Relatively New Doppler Echocardiographic Parametermentioning
confidence: 99%
“…[8][9][10][11][12][13][14] There is a limited number of studies on cardiovascular complications of asthma. In primary bronchopulmonary diseases, hypoxia-induced changes may cause PAS to increase by triggering remodeling in the pulmonary vascular structure.…”
mentioning
confidence: 99%